Il Segretario, lo Statista. Aldo Moro dal centro-sinistra alla solidarietà nazionale - Pierluigi Totaro (Scuola delle Scienze Umane e Sociali. Quaderni, 2019)
Aldo Moro, General Secretary of the Christian Democracy, Prime minister in an alliance of center-left, strategist of the government agreement with the Communist Party and finally victim of the political terrorism. Looking at two different stages of Italian political life - the season of center-left coalition and the tragic story of the armed struggle - this volume traces, from multiple perspectives, the tormented path of the leader politician that best sums up the Italian history of the second post-war period.